Potential of Bacillus spp. Isolates as Biological Control Agents Against Rhizoctonia solani, the Causal Agent of Sheath Rot in Maize (Zea mays L.) - Salma Alfiani Nadiva; Yenny Wuryandari; Tri Mujoko (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the effectiveness of laboratory-collected Bacillus spp. isolates against Rhizoctonia solani, the causal agent of maize sheath blight, under both in vitro and in vivo conditions, as available information on their efficacy remains limited. The in vitro assay was conducted using the dual culture method with five Bacillus spp. isolates, namely Bcz-14, Bcz-16, Bcz-20, Bcz-21, and Bcz-30, to assess their inhibitory activity against R. solani. The results showed that all isolates were able to inhibit pathogen growth, although the percentage of inhibition varied among isolates. Isolate Bcz-14 exhibited the highest mean inhibition, while isolates Bcz-16 and Bcz-21 were selected for the in vivo assay based on a combination of mean inhibitory activity and consistency across replications. The in vivo assay was conducted using the two selected isolates with different application times, namely seven days before planting and at planting. The results indicated that treatment B1T1, consisting of Bcz-16 applied seven days before planting, showed a greater tendency to suppress disease development, as indicated by a longer incubation period and the lowest disease intensity of 17.78%. These findings suggest that isolate Bcz-16 has potential for further development as a biological control candidate for maize sheath blight. However, further evaluation under field conditions is required to confirm its effectiveness.